Alkyl chain length of quaternized SBA-15 and solution conditions determine hydrophobic and electrostatic interactions for carbamazepine adsorption - Jin-Kyu Kang; Hyebin Lee; Song-Bae Kim; Hyokwan Bae (Scientific Reports, 2023)
Abstract Santa Barbara Amorphous-15 (SBA) is a stable and mesoporous silica material. Quaternized SBA-15 with alkyl chains (QSBA) exhibits electrostatic attraction for anionic molecules via the N+ moiety of the ammonium group, whereas its alkyl chain length determines its hydrophobic interactions. In this study, QSBA with different alkyl chain lengths were synthesized using the trimethyl, dimethyloctyl, and dimethyoctadecyl groups (C1QSBA, C8QSBA, and C18QSBA, respectively). Carbamazepine (CBZ) is a widely prescribed pharmaceutical compound, but is difficult to remove using conventional water treatments. The CBZ adsorption characteristics of QSBA were examined to determine its adsorption mechanism by changing the alkyl chain length and solution conditions (pH and ionic strength). A longer alkyl chain resulted in slower adsorption (up to 120 min), while the amount of CBZ adsorbed was higher for longer alkyl chains per unit mass of QSBA at equilibrium. The maximum adsorption capacities of C1QSBA, C8QSBA, and C18QSBA, were 3.14, 6.56, and 24.5 mg/g, respectively, as obtained using the Langmuir model. For the tested initial CBZ concentrations (2–100 mg/L), the adsorption capacity increased with increasing alkyl chain length. Because CBZ does not dissociate readily (pKa = 13.9), stable hydrophobic adsorption was observed despite the changes in pH (0.41–0.92, 1.70–2.24, and 7.56–9.10 mg/g for C1QSBA, C8QSBA, and C18QSBA, respectively); the exception was pH 2. Increasing the ionic strength from 0.1 to 100 mM enhanced the adsorption capacity of C18QSBA from 9.27 ± 0.42 to 14.94 ± 0.17 mg/g because the hydrophobic interactions were increased while the electrostatic attraction of the N+ was reduced. Thus, the ionic strength was a stronger control factor determining hydrophobic adsorption of CBZ than the solution pH. Based on the changes in hydrophobicity, which depends on the alkyl chain length, it was possible to enhance CBZ adsorption and investigate the adsorption mechanism in detail. Thus, this study aids the development of adsorbents suitable for pharmaceuticals with controlling molecular structure of QSBA and solution conditions.